Gender Analysis of Ginger Cultivation in Ri-Bhoi district of Meghalaya - Kalai, Kankabati; Devarani, Loukham (Indian Journal of Hill Farming, 2018)
Gender has become key issue in agricultural research and activities which mostly focus on differences in gender role in agricultural production. Gender analysis is a tool for understanding and documenting the differences in gender roles, activities, needs, and opportunities in a given context. The study was carried out during 2014 in Nogladew village of Ri-Bhoi district of Meghalaya. Data were collected using Participatory Rural Appraisal (PRA) techniques and Focus Group Discussions (FGDs) from two groups, one each for women and men farmers. It was observed that both men and women actively participate in ginger cultivation. The extents of participation of the genders in different activities as well as the perception of the two genders regarding this vary but all do participate actively. Ensuring gender equity and gender balance in extension activities as well as gender mainstreaming of extension programmes is recommended.